Guide Strand 3′‐End Modifications Regulate siRNA Specificity. (7th November 2016) - Valenzuela, Rachel A. P.; Onizuka, Kazumitsu; Ball‐Jones, Alexi A.; Hu, Tiannan; Suter, Scott R.; Beal, Peter A.
Abstract: Short interfering RNA (siRNA)‐triggered gene knockdown through the RNA interference (RNAi) pathway is widely used to study gene function, and siRNA‐based therapeutics are in development. However, as the guide strand of an siRNA can function like a natural microRNA (miRNA), siRNAs often repress hundreds of off‐target transcripts with complementarity only to the seed region (nucleotides 2–8) of the guide strand. Here, we describe novel guide strand 3′‐end modifications derived from 1‐ethynylribose (1‐ER) and copper‐catalyzed azide–alkyne cycloaddition reactions and evaluate their impact on target versus miRNA‐like off‐target knockdown. Surprisingly, when positioned at the guide strand 3′‐end, the parent 1‐ER modification substantially reduced off‐target knockdown while having no measurable effect on on‐target knockdown potency. In addition, these modifications were shown to modulate siRNA affinity for the hAgo2 PAZ domain. However, the change in PAZ domain binding affinity was not sufficient to predict the modification's effect on miRNA‐like off targeting. Abstract : The End : 1‐Ethynyl ribose (1‐ER) was incorporated into a short interfering RNA (siRNA) guide strand at the 3′‐end and further modified by azide–alkyne cycloaddition reactions. 1‐ER at the 3′‐terminal position significantly reduced miRNA off targeting while maintaining on‐target knockdown potency.